Identification and Characterization of Two Novel ISCR1-Associated Genes, dfrA42 and dfrA43, Encoding Trimethoprim-Resistant Dihydrofolate Reductases - Li, Ling (Antimicrob Agents Chemother, 2021)
Two novel ISCR1-associated dfr genes, dfrA42 and dfrA43, were identified from trimethoprim (TMP)-resistant Proteus strains and were shown to confer high levels of TMP resistance (MIC, ≥1,024 mg/liter) when cloned into Escherichia coli isolates. These genes were hosted by complex class 1 integrons, suggesting their potential for dissemination. Analyses of enzymatic parameters and TMP affinity were performed, and the results suggested that the mechanism of TMP resistance for these novel dihydrofolate reductases (DHFRs) is the reduction of binding with TMP.